N-1 regioselective Michael-type addition of 5-substituted uracils to (2-hydroxyethyl) acrylate - Boncel, Sławomir; Osyda, Dominika; Walczak, Krzysztof Z. (Beilstein Journal of Organic Chemistry, 2007)
N-1 regioselective Michael-type addition of 5-substituted uracils to (2-hydroxyethyl) acrylate is presented. The reactions were performed in polar aprotic solvents and with avoidance of polymerization of acrylic substrate. The obtained adducts may serve as versatile substrates for further functionalization, e.g. into (3-uracil-1-yl)propanoic acids or transformations, with participation of hydroxyl group, into ester-conjugated acyclic nucleosides.